Characterization of Polymeric Microneedle Arrays for Transdermal Drug Delivery - KERİMOĞLU, OYA (PUBLIC LIBRARY SCIENCE, 2013)
Microfabrication of dissolvable, swellable, and biodegradable polymeric microneedle arrays (MNs) were extensively investigated based in a nano sensitive fabrication style known as micromilling that is then combined with conventional micromolding technique. The aim of this study was to describe the polymer selection, and optimize formulation compounding parameters for various polymeric MNs. Inverse replication of micromilled master MNs reproduced with polydimethylsiloxane (PDMS), where solid out of plane polymeric MNs were subsequently assembled, and physicochemically characterized. Dissolvable, swellable, and biodegradable MNs were constructed to depth of less than 1 mm with an aspect ratio of 3.6, and 1/2 mm of both inter needle tip and base spacing. Micromolding step also enabled to replicate the MNs very precisely and accurate. Polymeric microneedles (MN) precision was ranging from +/- 0.18 to +/- 1.82% for microneedle height, +/- 0.45 to +/- 1.42% for base diameter, and +/- 0.22 to +/- 0.95% for interbase spacing. Although dissolvable sodium alginate MN showed less physical robustness than biodegradable polylactic-co-glycolic acid MN, their thermogravimetric analysis is of promise for constructing these polymeric types of matrix devices.
Keywords: DISSOLVING MICRONEEDLES; FABRICATION; GEOMETRY; NEEDLES